Microbial reduction of Cr(VI) in the presence of chromate conversion coating constituents - Iannuzzi, Mariano; Miller, R.; Giai, C.; Monty, C.; Senko, J. (Taylor & Francis, 2016)
The reduction of Cr(VI) by the metal-reducing bacterium Shewanella oneidensis MR-1 was evaluated, to determine the potential for exploiting Cr(VI) bioreduction as a means of treating chromate conversion coating (CCC) waste streams. Inclusion of Cr(VI) at concentrations ≥1 mM inhibited aerobic growth of S. oneidensis, but that organism was able to reduce Cr(VI) at a concentration of up to 1 mM under anaerobic, nongrowth conditions. S. oneidensis reduced Cr(VI) in the presence of common CCC constituents, with the exception of ferricyanide, when these CCC constituents were included at concentrations typical of CCC waste streams. Ferricyanide inhibited neither aerobic growth nor metabolism under aerobic, nitrate- or iron-reducing conditions, suggesting that the ferricyanide-depended inhibition of Cr(VI) reduction is not due to broad metabolic inhibition, but is specific to Cr(VI) reduction. Results indicate that under some conditions, the activities of metal-reducing bacteria, such as S. oneidensis, could be exploited for the removal of Cr(VI) from CCC waste streams under appropriate conditions.